Design and preparation of a ternary MoC-QDs/C/Mo–S heterojunction for enhanced eosin Y-sensitized photocatalytic hydrogen evolution. (18th June 2021) - Li, Teng; Yan, Teng; Jin, Zhiliang
Abstract : Carbon film contributes to the separation of photogenerated carriers in the process of photocatalytic hydrogen evolution. Abstract : The catalyst MoC-QDs/C has a sufficient surface area and a unique lamellar structure, which provides a suitable position for the loading of Mo–S, so that the close contact and interfacial compatibility between MoC-QDs/C and Mo–S, and the smooth transfer of electrons through the carbon film (C) can be ensured. The catalyst MoC-QDs/C contains a large number of carbon films, and the carbon films have excellent conductive properties, so it can be used as a transfer channel for electrons to be transferred effectively, and the transferred electrons can be transmitted to MoC-QDs in time. The MoC-QDs act as the catalytic active center, which can effectively reduce H + to H2 by the obtained electrons. This unique design can effectively separate the photogenerated electron-holes and promote the photocatalytic splitting of water for hydrogen production. By optimizing the composite catalyst, the best composite material 10%-MCC/M–S was obtained, which showed excellent hydrogen production activity (198.15 μmol) that was 2.67 times that of pure Mo–S (74.29 μmol) within 5 h, and the stability of the catalyst was proved by the cycle experiment. This work offers a new strategy and direction for the application of carbon films in the field of photocatalytic water decomposition for hydrogen production.